Staphylococcus aureus agr Genotypes with Enterotoxin Production Capabilities Can Resist Neutrophil Bactericidal Activity - Mullarky, I. K. (American Society for Microbiology, 2001)
Staphylococcus aureus pathogenicity is mainly due to the production of a number of secreted and cell surface-associated proteins under the regulation of the agr gene. A region of the agr gene was used to subgroup S. aureus strains according to restriction fragment length polymorphisms. Additionally, strains were subtyped according to the coagulase gene in order to strengthen discriminatory power. Virulence capabilities of agr genotype subgroups were evaluated using an in vitro neutrophil bactericidal assay, which showed that prevalent genotypes were significantly better at evading this primary host defense. Multiplex PCR was then used to detect enterotoxin genes among the genotype subgroups in order to determine possible virulence candidates that enable strains to combat neutrophil killing. The prevalent genotype strains were found to possess higher production capabilities for enterotoxin A than did low-prevalence strains. The significance of enterotoxin A production capabilities in affecting pathogenicity of S. aureus strains was evaluated and found to have a profound effect on neutrophil killing abilities. The use of a large epidemiological database as a tool for subgrouping strains with varying degrees of pathogenicity has allowed the identification of relevant and previously undefined virulence factors that affect a pathogen's capability to overcome host immune defenses.